EXPLORING JAVANESE ISLAM: “THE ACCULTURATION OF RELIGIOUS DOCTRINE WITH CULTURAL RITUALS" - Lestari, Sri; Mukaromah, Choirunisa; Dwi, Melan Deciani; Amaliah, Putti Nur; Parhan, Muhamad (KOMUNITAS, 2023)
The entry of Islam into Java provided a new culture in the Javanese tradition regarding the teachings adopted by the people, this was due to acculturation and in the process the two teachings could coexist, in Javanese society itself it is known as Kejawen. This study discusses the meeting between Islam and Javanese culture which aims to find out more about the differences between Islamic teachings and Kejawen culture. The method used in finding the bright spot of this problem uses a qualitative method through a literature review approach. Based on the research conducted, it was found that the acculturation of Islam with Javanese culture originated from the spread of Islam by Wali Songo using culture as an intermediary, giving rise to a new understanding of Islam and the formation of Kejawen groups. In essence, the spread of Islam in Java was packed with Javanese cultural traditions and rituals.